2020
DOI: 10.22271/chemi.2020.v8.i6f.10799
|View full text |Cite
|
Sign up to set email alerts
|

Path analysis studies of EMS-mutagenized mutant population of hexaploid wheat (Triticum aestivum L.)

Abstract: Mutated genetic resources play a crucial role and are of utmost importance in gene/allele characterization. Currently, hexaploid wheat mutated resources are rarely available. In the present investigation, a mutated population comprising 1,536 EMS-induced mutation lines (M7 generation) of bread wheat (Triticum aestivum L.) were used as an experimental material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…This analysis is very important in assessing selection characteristics due to the insufficiency of correlation analysis in this study. Fadhli et al (2020) demonstrated the effectiveness of this analysis on maize during drought stress testing, while Baye et al (2020), Bisht et al (2020), Nada et al (2021), andFarid et al (2021) demonstrated the effectiveness of this analysis on wheat mutant. The number of productive tillers and grain weight per panicle were identified as characteristics with the potential to support the yield through path analysis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This analysis is very important in assessing selection characteristics due to the insufficiency of correlation analysis in this study. Fadhli et al (2020) demonstrated the effectiveness of this analysis on maize during drought stress testing, while Baye et al (2020), Bisht et al (2020), Nada et al (2021), andFarid et al (2021) demonstrated the effectiveness of this analysis on wheat mutant. The number of productive tillers and grain weight per panicle were identified as characteristics with the potential to support the yield through path analysis.…”
Section: Discussionmentioning
confidence: 98%
“…Meanwhile, the yield potential of cereal crops, such as corn and sorghum is largely determined by the size of the cob and panicle since they rely on apical dominance for growth (Dixit et al 2014). According to Nukasani et al (2013), Ayer et al (2017), Bisht et al (2020), Nada et al (2021), andFarid et al (2021), grain weight per panicle is another important trait that contributes to the wheat yield. The combination of these two characteristics with the yield is an optimal choice in developing the selection index.…”
Section: Discussionmentioning
confidence: 99%